Quality management and socio-economic objectives in the construction of the Gautrain - Ayandibu, Olabode Gbenga (My University, 2011)
Apartheid caused segregation and inequality in technical and managerial skills in all sectors in South Africa. Because of the unsatisfactory skills level in South Africa, the post-apartheid government decided to use the construction sector as one of the ways of providing development for sustainability and redistribution of wealth. Job creation, one of the ways of alleviating poverty by the government, has been carried out effectively by employment-intensive methods of construction for small and technically simple projects. Gautrain is an exception because it is high standard infrastructure owned by the government and yet it has similar socio-economic goals attached to it. Despite the requirement of high quality in the Gautrain, these socio-economic development goals have been exceeded by the execution team without compromising the quality. In this report, the method of quality management of Gautrain is explored to understand the reason for the success in the implementation of the two objectives that may conventionally seem difficult to reconcile in very large and traditionally equipment intensive projects – quality and socio-economic goals. The findings of this study are that the execution of major infrastructure projects can achieve significant socio-economic goals and high quality, which can be achieved by ensuring that the design team puts into place policies and executes the project to ensure that the objectives are met. These principles can be used to guide a wide range of infrastructure projects in the future. The importance of training at all levels during the execution of projects is shown in this report. This report has shown the possibilities of integrating non-compliant small contractors into an ISO9000 compliant project in a supply chain management system where the main contractor is commercially and contractually driven to deliver.